Gastric Emptying of Liquids in Children. Issue 3 (March 2016) - Hauser, Bruno; Roelants, Mathieu; De Schepper, Jean; Veereman, Gigi; Caveliers, Vicky; Devreker, Thierry; De Greef, Elisabeth; Vandenplas, Yvan
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objectives: The present study was performed to determine normal values for gastric half-emptying time (t1/2 GE) of liquids in healthy children. Methods: Gastric emptying (GE) of a standardized test milk-drink measured with 99m technetium scintigraphy and the 13 C-acetate breath test ( 13 C-ABT) was compared in 19 children ages between 4 and 15 years with upper gastrointestinal symptoms. The 13 C-ABT was subsequently used to determine normal values for GE of the same liquid test meal in 133 healthy children ages between 1 and 17 years. Results: In the group of children with upper gastrointestinal symptoms, the results showed a significant correlation ( r = 0.604, P = 0.0006) between t1/2 GE measured with both techniques. In the group of healthy children, the results of t1/2 GE showed that there was no influence of age, sex, weight, height, and body mass index on GE. Conclusions: Normal values for GE of a standardized test milk-drink in healthy children were determined with the 13 C-ABT. This technique is considered reliable and is well accepted by the patients.